ANALISIS ASPEK SOSIAL DAN ASPEK MORAL DALAM NOVEL PESTA TERAKHIR KARYA ZULKIFLI L. MUCHDI - Awan Wicaksono; Rian Damariswara (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Novel is one of literature work that often show various of life story of the main character. This is because the novel it is one of result of emotional thinking of author, What that author feel inside or outside him/her will affect the result of what novel show. Outside emotional thinking may come from the surrounding environtment and society. So novel sometimes will show some reality like it is in real life that written in aesthetic language. Therefore novel sometimes not off from sosial aspect and moral aspect that happen in real life. Novel Pesta Terakhir tell the story of Wike that struggle helping her families by looking for money to pay the debt that cause their home to be confiscated, as the time goes by their house bought by Aunt Rose, and with this tactic will make Wike come and negotiate with her and then lure Wike into trap of human trafficking. Thus the purpose of this research is to find the sosial aspect and moral aspect in novel Pesta Terakhir work from Zulkifli L. Muchdi, this research method is using qualitative with study literature technique. Result of this research is there are social aspect economy, education, culture, politic, and society. Likewise, there are moral aspects, namely prostitution, drug use, and human trafficking. Keywords: social aspect, moral aspect, novel pesta terakhir